PENYELESAIAN SENGKETA PERALIHAN TANAH ULAYAT DI DESA SIGAPITON, KECAMATAN AJIBATA, KABUPATEN TOBA - Vivianne I R Nadeak; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The Regional Regulation of North Sumatra Number 5 in 2018 concerning the North Sumatra TourismDevelopment Master Plan from 2017-2025, in clause 17 letter b says that Sigapiton Village is one of thetourism development areas of North Sumatra. And in 2017 the State represented by the RegionalGovernment of Toba Regency built a tourist area called The Kaldera Toba on the Customary Land ofSigapiton Village. The government said that their customary land had been transferred by the ancestors ofSigapiton Village in 1952 to the State and had become State land in that year. The people of SigapitonVillage asked for documents on the transfer of their customary land but the Regional Government of TobaRegency could not show the documents on the transfer of their customary land to the State. The purpose ofthis research is to resolve the problem of the transfer customary land with the state, where the Sigapitonvillage community wants their rights of their Customary land back so they could manage it and staterecognizes the existence of their customary land so there is no more disputes between the Sigapiton villagecommunity to state and state to another village community.The method that used in this research is Sociological can be research that could see the correlationbetween law and society, so as to reveal the effectiveness of the enactment of law in society and identifyunwritten laws that apply to society. This research was conducted in Sigapiton Village, Toba Regency. Thesources of data that used are primary data and secondary data, with data collection techniques in this studyare observation, questionnaires, interviews and literature review.The result of the author's research is that the Sigapiton Village Community had negotiated with thegovernment. In terms of the first negotiation and second did not produce any results. And in the thirdnegotiation, the government promised to gave back the Customary Land of the Sigapiton Village Community ofabout 400ha. The approximately 400ha should be returned in a clear legal status that had certificate ofreturned land with clear boundaries by National Land Agency (BPN).Keyword: Transition, Customary Land, Dispute Settlement.